Förderung der Schlüsselkompetenzen im universitären Grammatikunterricht durch den Einsatz der LdL-Methode – Ergebnisse einer Fragebogenstudie - Janicka, Monika (Neofilolog, 2023)
In the knowledge economy, the memorization of facts and procedures is important but not sufficient. In order to responding to changes in society and the economy it becomes necessary to develop key competences. Competences-oriented education introduces innovative forms of teaching and learning based on the constructivist learning approach, such as the LbT-Method (Learning by Teaching /Lernen durch Lehren/), which gives the students the opportunity to learn by doing. The article introduces the results of a survey which was conducted during the third semester of a “Grammar in Communication” course at the faculty of Applied Linguistics at Maria Curie-Skłodowska University in Lublin. According to the students’ assessment, their participation in this course enhanced their literacy, multilingual, personal, social and learning-to-learn competences, as well as their entrepreneurial competence. The results of this survey will be used to optimize the course design in the future.